Improving the Psychological Well-Being of Social Media Users Through Group Counseling Services Using Stress Inoculation Techniques on Students - Dlt, Hapni Madini; Nasution, Fauziah (Journal of Social Work and Science Education, 2025)
This study aims to determine the effectiveness of group guidance services using the Stress Inoculation Training (SIT) technique in enhancing the psychological well-being of social media users at Budisatrya High School Medan. The research adopts a quantitative approach with a one-group pre-test - post-test design to evaluate changes before and after the intervention. The participants consisted of eight students identified with varying levels of psychological well-being, as assessed through an initial screening process. The intervention was conducted through a series of structured group counseling sessions integrating SIT phases: conceptual education, skills acquisition, and application. The statistical analysis revealed a significant improvement in psychological well-being, with the average score increasing from 91.00 (pretest) to 107.63 (post-test). The normality test indicated that the post-test data were normally distributed, while the pretest data were not. The homogeneity of variance was confirmed with a significance value of 0.533, allowing the use of parametric tests. The paired sample t-test yielded a value of t = -13.749 and Sig. = 0.000, indicating a statistically significant difference between the pre-test and post-test scores. These findings suggest that group guidance services incorporating SIT are effective in improving students’ psychological well-being, particularly in managing stress related to excessive social media use. The study underscores the importance of integrating psychological resilience training into school-based mental health programs to address the growing psychosocial challenges in the digital era.